Analisis Produktivitas Produksi pada Usaha UMKM Meubel Jepara - Sukmana, Rizal Wiri; Ichsan, M. Nurfadillah; Fadillah, M. Rizki (Jejak digital: Jurnal Ilmiah Multidisiplin, 2026)
This study aims to analyze production productivity in furniture SMEs in Jepara and identify the factors affecting it. A descriptive qualitative approach with a case study method was employed. Data were collected through in-depth interviews, observations, and documentation, then analyzed descriptively. The findings indicate that production productivity is influenced by workforce skills, production technology, raw material availability, work time efficiency, and production management. Most furniture SMEs still rely on simple production equipment, resulting in suboptimal production processes. In addition, delays in raw material supply, shortages of skilled workers, and unstructured production systems are the main constraints affecting production targets. Nevertheless, Jepara furniture SMEs have strong development potential due to their product quality and high market demand. Production productivity can be improved through equipment modernization, workforce skill enhancement, effective production management, and more efficient work process management to strengthen the competitiveness of Jepara’s furniture industry.